Vulvar melanoma: relevant aspects in therapeutic management - Adriana Bittencourt Campaner; Gustavo Leme Fernandes; Fernanda de Araujo Cardoso; John Verrinder Veasey (Sociedade Brasileira de Dermatologia, 2017)
Abstract Cancer of the vulva accounts for at least 1% of malignant neoplasms among women. Although rare, vulvar melanoma is the second most common histological type of vulvar cancer, representing 7-10% of all malignant vulvar neoplasms. Initial symptoms are non-specific and complete excision of the lesion is indicated in cases with suspected diagnosis. Prognosis of patients with these neoplasms is poor and remains unchanged despite the treatment approach. Hemivulvectomy with lymph node dissection is the current procedure of choice, associated or not with adjuvant therapies. We report two cases of patients presenting with late diagnosed vulvar melanoma and the relevant aspects in their therapeutic management.